DESIGN AND EVALUATION OF NOVEL TOPICAL GEL OF TINOSPORA CORDIFOLIA AS ANTIMICROBIAL AGENT - D DORLE, ABHISHEK; S SWAMI, KUMAR; K NAGARE, SUJIT; R HYAM, SUPRIYA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The present study deals with topical formulations of a bioactive extract of Tinospora cordifolia and its evaluation. Methods: Dried, powdered stem was extracted with chloroform using ultra-sonication method for 3 hrs. Topical formulations like gels containing chloroform extract were formulated using various gelling agents. These gels were evaluated for physicochemical parameters, viscosity, spreadaibility, and antimicrobial activity. Results: A topical gel was successfully formulated containing bioactive chloroform extract of T. cordifolia. The gel was very effective as antimicrobial formulations. Conclusion: These kinds of formulations can be very promising wound healing medicines with ease of use and no side effects. Keywords: Topical gel, Tinospora Cordifolia, Anitmictobial